2020
DOI: 10.1038/s41398-020-0788-8
|View full text |Cite
|
Sign up to set email alerts
|

Chronic inhibition of GABA synthesis in the infralimbic cortex facilitates conditioned safety memory and reduces contextual fear

Abstract: Accurate discrimination between danger and safety cues is essential for survival. Recent findings in humans indicate that patients suffering from anxiety disorders cannot reliably use safety cues in order to inhibit fear responses. However, the neuroanatomical pathways of conditioned safety are still unclear. Aim of the present study was to investigate whether chronic inhibition of GABA synthesis in the infralimbic (IL) cortex, a critical region for fear inhibition, would lead to enhanced conditioned safety me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 80 publications
(117 reference statements)
1
3
0
Order By: Relevance
“…While the prospective safety cue had no effects on the startle magnitude pre-conditioning, it significantly attenuated the startle magnitude after single-cued safety conditioning in male and female rats. This, as well as data from other studies applying the same type of training indicate that a positive associative memory to the safety cue was formed ( Kong et al, 2014 ; Kreutzmann et al, 2020a , 2020b , 2021 ; Rogan et al, 2005 ; Camp et al, 2012 ; Ostroff et al, 2010 ; Kreutzmann and Fendt, 2020 ). We further observed that vehicle-treated rats, regardless of sex, expressed potentiated context startle magnitudes following safety conditioning.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…While the prospective safety cue had no effects on the startle magnitude pre-conditioning, it significantly attenuated the startle magnitude after single-cued safety conditioning in male and female rats. This, as well as data from other studies applying the same type of training indicate that a positive associative memory to the safety cue was formed ( Kong et al, 2014 ; Kreutzmann et al, 2020a , 2020b , 2021 ; Rogan et al, 2005 ; Camp et al, 2012 ; Ostroff et al, 2010 ; Kreutzmann and Fendt, 2020 ). We further observed that vehicle-treated rats, regardless of sex, expressed potentiated context startle magnitudes following safety conditioning.…”
Section: Discussionsupporting
confidence: 75%
“…We further observed that vehicle-treated rats, regardless of sex, expressed potentiated context startle magnitudes following safety conditioning. This suggests that rats were fear conditioned to the context in which electric stimuli had previously been received ( Kreutzmann and Fendt, 2020 ; Kreutzmann et al, 2021 ). Of note, the pre-conditioning IN application procedures seem to generally attenuate contextual fear conditioning in both treatment groups.…”
Section: Discussionmentioning
confidence: 99%
“…Our results demonstrate a robust protocol for safety conditioning and underscore that the ASR is a useful tool to measure the effects of conditioned safety in rats. Of note, other studies have also applied this type of conditioning (explicit unpairing) as safety protocol (Rogan et al 2005;Pollak et al 2008;Pollak et al 2010;Ostroff et al 2010;Kreutzmann et al 2019;Kreutzmann and Fendt 2020). In contrast to these studies, we added a pseudo-conditioning group in order to assess non-associative effects of the light cue and to control for potential unspecific effects of the IL/ PL manipulations.…”
Section: Discussionmentioning
confidence: 99%
“…Assuming that statistical power was 95%, significance level was 0.05 and effect size was 0.5 (Cohen's standard medium), it was estimated that at least 210 participants (105 participants per group) would be required to show a statistically significant difference in medication use or rationality between two groups. 15 Statistical analyses were performed with SPSS 22.0 (IBM Inc.).…”
Section: Discussionmentioning
confidence: 99%